Implementation of Behavioral Guidance For Inmates at Class IIB Kabanjahe State Prison - Benny Nova; Abdul Razak Nasution; Henry Aspan (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
The development of prisoners is an effort or a series of steps taken to empower inmates to become individuals with good morals, skills, and the ability to live independently according to the responsibilities given to them. Therefore, the author wants to study how behavioral development is implemented for correctional inmates in Class IIB Kabanjahe Detention Center. The classification of correctional institutions: Correctional institutions or prisons are Technical Implementation Units (UPT) under the Directorate General of Corrections of the Ministry of Immigration and Corrections, formerly the Ministry of Law and Human Rights. Prisons can be divided into several types by considering certain aspects. Correctional institutions can be categorized based on their facilities and capacity. This study applies a qualitative approach, which aims to examine a problem without intending to prove or disprove a previously formulated hypothesis, but rather by processing data and analyzing the issue in a non-numerical manner.